1922 Miss. Laws 235 - (:unkn) unknown (My University, 1922)
Ch. 181, § 10(b): It shall be unlawful for any person to shoot wild water fowl with any shotgun of larger bore than number ten, or with any rifle or any gun which can be shot from the shoulder.
Keywords: HUNTING REGULATION